2013
DOI: 10.1088/2043-6262/4/2/025001
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of curcumin-loaded pluronic F127/chitosan nanoparticles for cancer therapy

Abstract: Nanoparticles (NPs) have been proven to be an effective delivery system with few side effects for anticancer drugs. In this study, curcumin-loaded NPs have been prepared by an ionic gelation method using chitosan (Chi) and pluronic®F-127 (PF) as carriers to deliver curcumin to the target cancer cells. Prepared NPs were characterized using Zetasizer, fluorescence microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Our results showed that the encapsulation efficiency of cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…The EE% of curcumin in CaANCs reached up to 95%. This value is higher or comparable to those reported for other curcumin-loaded nanoparticles: 80% to 82% in liposomes [63], less than 90% in mPEG-PLGA nanoparticles [64], 91% for curcumin-loaded PLGA nanospheres [65], 62% with curcumin-loaded pluronic F127/ chitosan nanoparticles [66], 94% for curcumin loaded PLGA nanoparticles [67]. An EE% of 52% was described in other alginate formulations [35] and 68% in alginate chitosan nanocapsules [14].…”
Section: Curcumin Encapsulation In Caancssupporting
confidence: 74%
“…The EE% of curcumin in CaANCs reached up to 95%. This value is higher or comparable to those reported for other curcumin-loaded nanoparticles: 80% to 82% in liposomes [63], less than 90% in mPEG-PLGA nanoparticles [64], 91% for curcumin-loaded PLGA nanospheres [65], 62% with curcumin-loaded pluronic F127/ chitosan nanoparticles [66], 94% for curcumin loaded PLGA nanoparticles [67]. An EE% of 52% was described in other alginate formulations [35] and 68% in alginate chitosan nanocapsules [14].…”
Section: Curcumin Encapsulation In Caancssupporting
confidence: 74%
“…PF is highly soluble in water and dispersible across a broad spectrum of solvents and temperatures, enabling its utilization across a diverse array of applications [27]. However, using polymeric micelles with the sole co-polymer as prolonged drug carriers is not feasible in practice due to the tendency of particle aggregation and physical deterioration under different concentrations and temperatures [28]. The outer shell of polymeric micelles performs a pivotal function in enhancing the bioactivity and characteristics of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the stability of Pluronic® micelles can be significantly improved after being coated with a chitosan layer [58,59]. The use of chitosan provides numerous advantages due to its biodegradability, biocompatibility, ease of technical application, versatility and low toxicity.…”
Section: Chitosanmentioning
confidence: 99%